2021
DOI: 10.1192/j.eurpsy.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Examining the association between exposome score for schizophrenia and functioning in schizophrenia, siblings, and healthy controls: Results from the EUGEI study

Abstract: Background: A cumulative environmental exposure score for schizophrenia (exposome score for schizophrenia: ES-SCZ) may provide potential utility for risk stratification and outcome prediction. Here, we investigated whether ES-SCZ was associated with functioning in patients with schizophrenia spectrum disorder, unaffected siblings, and healthy controls. Methods: This cross-sectional sample consisted of 1261 patients, 1282 unaffected siblings, and 1525 healthy controls. The Global Assessment of Functioning (GAF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 60 publications
7
14
0
Order By: Relevance
“…The current study offers a template for future studies, which may incorporate symptom ratings alongside PRS or putative phenotypic markers (such as actigraphy-based rest-activity rhythms) to generate new screening instruments and risk prediction algorithms. Furthermore, whilst we focus mainly on selected intrinsic markers of vulnerability, we believe further research can incorporate other intrinsic dimensions (such as personality traits, functioning) and extrinsic markers, such as life events and adversity into a more comprehensive model [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study offers a template for future studies, which may incorporate symptom ratings alongside PRS or putative phenotypic markers (such as actigraphy-based rest-activity rhythms) to generate new screening instruments and risk prediction algorithms. Furthermore, whilst we focus mainly on selected intrinsic markers of vulnerability, we believe further research can incorporate other intrinsic dimensions (such as personality traits, functioning) and extrinsic markers, such as life events and adversity into a more comprehensive model [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2021 ( 43 ) A population-based prospective cohort study in the Netherlands (NEMESIS-2) ES-SCZ showed a significantly better discriminative function (AUC = 0.84; LR − = 0.20; LR + = 3.86) than Emet and Esum ES-SCZ was associated with SCZ diagnosis with the highest OR (2.76 [95% CI = 2.20 – 3.46]) and the greatest explained variance ( R 2 = 14.03%) among 33 mental and physical health outcomes Erzin et al. , 2021a ( 48 ) Multinational study of individuals with SCZ, unaffected siblings, and control subjects (EUGEI and GROUP) ES-SCZ was associated with poor global functioning domains in control subjects, siblings, and patients in EUGEI, also after controlling for PRS-SCZ Results were replicated independently in GROUP Erzin et al. , 2021b ( 47 ) One-year follow-up study of individuals with FEP in Greece (Athens FEP Research Study) ES-SCZ was associated with poor global and specific functioning domains at baseline and 1 month, also after controlling for demographic, familial, and other environmental factors and clinical features ES-SCZ predicted poor improvement in symptom severity (particularly negative symptoms) from baseline to 1 month assessment AUC, area under the receiver operating characteristic curve; Emet, aggregate environmental score weighted by the meta-analytic estimates; Esum, environmental sum score; ES-SCZ, exposome score for schizophrenia; EUGEI, European Network of National Networks studying Gene-Environment Interactions in Schizophrenia; FEP, first-episode psychosis; GROUP, Genetic Risk and Outcome of Psychosis Study; LR, likelihood ratio; NEMESIS-2, Netherlands Mental Health Survey and Incidence Study-2; OR, odds ratio; PRS-SCZ, polygenic risk score for schizophrenia; SCZ, schizophrenia.…”
Section: Predictive Modeling Approach For Estimating Exposome Score F...mentioning
confidence: 97%
“…We have investigated the predictive performance and the utility of ES-SCZ in the general population cohort and independent samples of individuals with PSD ( Table 1 ). Overall, these studies show that ES-SCZ, an index of environmental predisposition, can be used to test gene × environment ( 44 ) and environment × environment ( 45 ) interactions, improve psychosis prediction and risk stratification in the general population ( 43 , 46 ), and enhance clinical outcome prognostication in individuals with PSD ( 47 , 48 ). ES-SCZ offers a practical and consistent solution that can be applied across independent samples (given consistent collection of exposures across samples) to yield comparable findings.…”
Section: Predictive Modeling Approach For Estimating Exposome Score F...mentioning
confidence: 97%
“…Moreover, the paradigm of the exposome was only recently investigated in the field of schizophrenia [ 63 , 178 , 179 , 180 ]. The exposome represents the entirety of the environmental vulnerability underlying the pathoetiology of schizophrenia spectrum disorders, to which an individual is exposed to throughout their life [ 178 , 180 , 181 ]. According to the exposome model, environmental factors are bi-directionally interlinked, such that cannabis use is associated with childhood adversity, the effects of urbanicity variables (such as population density, deprivation, etc.)…”
Section: Environmental Factorsmentioning
confidence: 99%